Comparative Analysis of the Evenness Properties of Yarn Spun Using a Sinusoidal Pressure Bar. Issue 16 (28th November 2022) - Xu, Duo; Fan, Hang; Chen, Ze; Gao, Chong; Liu, Keshuai; Fang, Jian; Xu, Weilin
ABSTRACT: In this study, a sinusoidal pressure bar was used as a method of increasing the rear draft ratio to produce high-quality and high-efficiency yarn. Traditional-ring-spun yarn, traditional-pressure-bar-spun yarn, and sinusoidal-pressure-bar-spun yarn (denoted as TRSY, TPBSY, and SPBSY, respectively) were compared. A geometrical analysis indicated that the control stress of the sinusoidal friction field prevented the moving roving from twisting. Subsequently, the fiber strand was combed by the sinusoidal structure of the pressure bar, improving the straight parallelism of the staple fibers. Therefore, the accelerated points of the fibers were concentrated and moved forward. The mechanical analysis indicated that three-dimensional stress is conducive to the control of the floating fiber movement. A motion simulation analysis revealed the three-dimensional stress was higher than that of other scenarios of fiber movement control. In particular, the three-dimensional control stress contributed to an excellent yarn regularity of the SPBSY. Furthermore, a multigroup of cotton yarns were spun under different rear draft ratios with and without the traditional pressure bar or sinusoidal pressure bar to conduct confirmatory experiments. The experimental results indicated that the SPBSY had the minimum coefficient of variance and fewer imperfections under high rear draft ratios after compared with the TRSY and TPBSY.